Advanced RF MEMS - Lucyszyn, S. (The Cambridge RF and microwave engineering series, 2010)
"An up-to-date guide to the theory and applications of RF MEMS. With detailed information about RF MEMS technology as well as its reliability and applications, this is a comprehensive resource for professionals, researchers, and students alike. Reviews RF MEMS technologies -- Illustrates new techniques that solve long-standing problems associated with reliability and packaging --Provides the information needed to incorporate RF MEMS into commercial products -- Describes current and future trends in RF MEMS, providing perspective on industry growth -- Ideal for those studying or working in RF and microwave circuits, systems, microfabrication and manufacturing, production management and metrology, and performance evaluation"--